Praktik Akad Nikah Bagi Mempelai Tunawicara dalam Perspektif Kompilasi Hukum Islam - Baihaqi, Achmad; Abadi, Said (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2021)
The author is interested in researching the practice of the marriage contract with the bride and groom who have limitations in pronouncing the contract (impaired), from practice in the field it is often the case that the marriage contract of the non-verbal bride is carried out by a representative but without a clear power of attorney, it is not entirely wrong. Because sometimes both parties believe that there will be no dispute in the appointment of representatives. The bride and groom base the implementation of their marriage contract on the encouragement of the community, clerics, customs, and indeed an agreement between the two parties. The approach method used in this paper is a juridical-normative approach in the study of fiqh. A juridical approach by examining legal rules and a normative approach in the study of fiqh is used in analyzing problems that occur in society. For provisions that require the granting of power in writing, basically it is not stipulated in the book of fiqh. In fact, fiqh explicitly stipulates that it can be in the form of words (عبارة) or in written form. There is nothing wrong with the provisions stipulated by the Compilation of Islamic Law, which are promulgated, following the rules of al-maslahah al-mursalah which have been explained or the concept in the book of Bughyah al-Mustarsyidn which says that government decrees which are not forbidden by the Shari'a must be obeyed physically and mentally. If it is against the Shari'a, such as obliging something that is haram, then it is enough to obey outwardly. In article 17 paragraph (3) of the KHI which reads "For the prospective bride and groom who suffers from speech impairment or deafness, consent can be stated in writing or signs that can be understood," so without a power of attorney there is nothing wrong or allowed. What is clear is that the marriage is still valid, the KUA does not require the speech-impaired bride and groom to make or show a power of attorney.